Roles of Occupant Behavior in Supporting Residential Energy Efficiency - Alfikhairina Jamil; Asdiana Asdiana; Destri Wulanda (Jurnal Ilmiah Multidisiplin Indonesia (JIM-ID), 2026)
Residential buildings are among the largest energy consumers worldwide, making residential energy efficiency an essential component of sustainable development and climate change mitigation. Whereas technological improvements have improved building energy performance, growing evidence suggests that occupant behavior plays a decisive role in determining actual energy consumption levels. This study intends to examine the role of occupant behavior in supporting residential energy efficiency through a comprehensive literature review. The findings indicate that occupant behavior significantly affects residential energy use and can either enhance or undermine the effectiveness of energy-efficient technologies. The review also identifies several intervention strategies that can promote energy conservation, including monetary rewards, personalized home energy audits, and comparative feedback programs. Among these, personalized feedback and community-based approaches demonstrate greater potential for sustaining long-term behavioral change, while financial incentives are generally more effective in the short term. The study concludes that achieving meaningful and lasting reductions in residential energy consumption requires an integrated approach that combines technological improvements with behavioral interventions. Incorporating occupant behavior into energy-efficiency policies and residential design strategies is therefore important for promoting sustainable energy use and decreasing environmental impacts.